Spatiotemporal single-cell analysis elucidates the cellular and molecular dynamics of human cornea aging - Dan Jiang; Ke Li; Yining Sun; Zicheng Zhang; Shuang Xie; Xintong Yu; Ruoqi Wang; Ying Feng; Qinxiang Zheng; Yajing Wen; Peter S. Reinach; Yuanyuan Du; et al. (Genome Medicine)
Abstract Background The human cornea is a transparent and uniquely ordered optical-biological system. Precise coordination of its cellular mechanisms is essential to maintain its transparency and functionality. However, the spatial, cellular and molecular architecture of the human cornea and its intercellular interactions during aging have not been elucidated. Methods We performed single-cell RNA sequencing (scRNA-seq) and single-cell SpaTial Enhanced REsolution Omics-sequencing (scStereo-seq) analysis in corneal tissue from eight eyes of donors aged 33-88 years to elucidate the spatiotemporal cellular and molecular dynamics of human cornea aging. Immunofluorescence staining and Western blotting were performed to validate the findings. Results Spatiotemporal single-cell analysis revealed the complex cellular landscape, spatial organization and intercellular communication within the human cornea. The subpopulations of major cell types of the cornea were elucidated with precise spatial positions. In particular, we identified novel subpopulations, mapped the spatial positioning of limbal stem cells within the limbal niche, and delineated the interactions between major cell types. We observed that three basal cell subsets migrate centripetally from the peripheral to the central cornea with age, suggesting the “spatiotemporal centripetal pattern” as a novel paradigm for the age-related migration of corneal epithelial cells. Furthermore, we elucidated the age-related, region-specific molecular and functional characteristics of the corneal endothelium, demonstrating differential metabolic capacities and functional properties between the peripheral and central regions. Conclusions As the first comprehensive spatiotemporal atlas, our work provides a valuable resource for understanding tissue homeostasis in the human cornea and advances research on corneal pathology, transplantation, senescence and regenerative medicine in the context of corneal aging.